Fazendo Arte na Geografia Escolar: O lugar-Cerrado nos Anos Iniciais do Ensino Fundamental - Azevedo, Mariângela Oliveira de (2024)
This research was based on desires present in our teacher training - for an educational action linked to the transformation of reality, permeated by teaching-learning processes with a view to an emancipatory education. In turn, these concerns have led me to school geography, a field in which I work as an elementary school teacher in the Early Years. From this experience, convergences emerge with academic-scientific production in the field of geography teaching and learning, which has long pointed to the need to appropriate teachinglearning practices with more meaning and significance and new languages, advancing in the observation of mechanistic methodologies that are disconnected from reality. These arguments led us to the initial problematizations for this research, through which we set out to think about teaching and learning in School Geography, indicating Art as a creative language for the construction of geographical knowledge in the classroom. To this end, we approached the Cerrado as a theme - essential and urgent geographical knowledge to be addressed in elementary school. The Cerrado is currently suffering the direct impact of neoliberalism, ideologized in the service of hegemonic interests, especially represented by economic activities aimed at agribusiness. The impact of this condition is multidimensional and requires interventions that permeate the classroom from the earliest school years, in order to form a critical awareness of the issue. In order to bring the complexities of the Cerrado closer to the teaching and learning of Geography in the Early Years of Primary School, our work proposed conceptualizing place-Cerrado, arguing in favour of place as a geographical concept that materializes the Cerrado in a meaningful way for students at this stage of education, as well as providing critical analyses of the world as a whole in an integrative way. The qualitative research consisted of investigative steps towards the goal of analyzing how teaching and learning about the Cerrado in school geography, using art as a creative language, can lead to emancipatory geographical knowledge in the Early Years. These steps were taken through the organization of three sections, the first two being a theoretical-methodological discussion about the relationship between the Cerrado, geographical place, Art and education, and the third dedicated to the analysis of a proposal for teaching and learning about the Cerrado in the Early Years of Primary School, a project carried out in a municipal public school in the city of Goiânia, with 5th grade students, in line with an action-research modality. Based on the lessons, we were able to draw up theoretically-based analyses of how the Cerrado place, associated with art as a creative language, could contribute to the construction of emancipatory geographical knowledge in the Early Years, a thesis presented by this research. In the methodological process, we used class diaries, analysis of activities and interviews as tools for analyzing the data. The entire discussion was based on the assumptions of historicaldialectical materialism as a method of analysis. As a result, the research has shown contributions that advance the need for critical teaching and learning and has been configured as a possible praxis, in School Geography, in approaching the Cerrado theme in an emancipatory way.